K0.5Na0.5VO3-SiO2 Co-sintering Agent of Ceramic Mg0.8Ti0.2O3 as Dielectric Material Candidate - Sefrilita Risqi Adikaning Rani; Ika Widya Wahyuningsih; Cindi Regita Cahyani (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2023)
This paper focuses on the characteristics of K0.5Na0.5VO3 (KNV) and SiO2 when added to Mg0.8Zn0.2TiO3 (MZT) material to reduce the sintering temperature. Initially, a single phase of Mg0.8Zn0.2TiO3 (MZT) was synthesized using the conventional solid-state reaction method at 850°C for 4 hours. Subsequently, (K0.5Na0.5)VO3 was formed as a single phase at a temperature of 500°C for 2 hours. The reduction of MZT sintering temperature was then carried out by adding K0.5Na0.5VO3 and SiO2 and sintering at 950°C for 4 hours. Adding K0.5Na0.5VO3 and SiO2 resulted in a maximum density value of 2.76 g/cc and an average grain size of 3 µm based on scanning electron microscopy (SEM) analysis. The optimal composition was found to be 0.7MZT-0.25KNV-0.05SiO2. X-ray diffraction (XRD) characterization using the Rietveld method revealed the presence of three phases: (Mg/Zn)TiO3, (K/Na)VO3, and MgTi2O5. Based on the results, it can be concluded that the (K/Na)VO3-SiO2 material can be effectively utilized as a sintering agent for (Mg/Zn)TiO3, reducing the sintering temperature of the material.